The enterprise DNA - Trotsyuk, Roman (2019)
Trotsyuk, R., & Santos, V. (2019). The enterprise DNA: Static and dynamic digital representation of organizations. International Journal of Engineering and Advanced Technology, 8(6), 5034-5038. https://doi.org/10.35940/ijeat.F9544.088619